Equisetum arvense: New Evidences Supports Medical use in Daily Clinic - Carneiro, Danilo Maciel; Jardim, Thiago Veiga; Araújo, Ymara Cássia Luciana; Arantes, Ana Carolina; Sousa, Andrea Cristina de; Barroso, Weimar Kunz Sebba; Sousa, Ana Luiza Lima; Cunha, Luiz Carlos da; Cirilo, Hérica Núbia Cardoso; Bara, Maria Teresa Freitas; Jardim, Paulo César Brandão Veiga (Pharmacognosy Reviews)
Relevant aspects to the clinical use of Equisetum arvense L. (common horsetail; EA) were reviewed and a search was conducted in the databases PubMed, LILACS, SciELO, Virtual Health Library, Cochrane and Scopus using the keyword “Equisetum arvense” for articles published from 2013 through 2017. So, eighty-eight articles that addressed the pharmacog nostic aspects and in vitro and in vivo biological activity, clinical trials with Equisetum arvense (EA) combined with other plants or alone, case reports concerning possible drug interactions and review studies were selected. The most relevant reported pharmacological effects in cluded antioxidant, anticarcinogenic, antimicrobial, vascular and ileum smooth muscle relax ant, analgesic, anti-inflammatory, antinociceptive, cytotoxic, antidiabetic, hepatoprotective, antilithiatic, dermatologic, wound healing, antileishmanial, diuretic, immunizing, platelet ag gregation inhibitory, osteoblast response-promoting, remineralizing, anxiolytic, sedative, anti convulsant and cognitive performance-stimulating activities. Five clinical trials demonstrated the efficacy of phytotherapeutic complexes containing EA, with three for treating benign prostate hyperplasia, one for chronic musculoskeletal pain and one describing the effects of a topical preparation on brittle nail syndrome. Three clinical trials tested EA alone; one analyzed its pharmacokinetics; another addressed the wound-healing effect of 3% EA ointment and a randomized double-blind clinical trial found that the diuretic effect of EA was superior com pared to the negative control and equivalent to treatment with hydrochlorothiazide (25 mg/ day) without changes in electrolyte excretion. Considering its long history of traditional use in several countries, in vivo and in vitro research and more recent clinical studies, EA meets the requisites for having well-defined medical applications with proven efficacy and acceptable safety.
Keywords: Common horsetail; Diuretic; Equisetum arvense; Medicinal plants; Phytotherapy